Ocular drug delivery systems based on nanotechnology: a comprehensive review for the treatment of eye diseases - Bairagi R.D.; Reon R.R.; Hasan M.M.; Sarker S.; Debnath D.; Rahman M.T.; Rahman S.; Islam M.A.; Siddique M.A.T.; Bokshi B.; Rahman M.M.; Acharzo A.K. (My University, 2025)
Ocular drug delivery is a significant challenge due to the intricate anatomy of the eye and the various physiological barriers. Conventional therapeutic approaches, while effective to some extent, often fall short in effectively targeting ocular diseases, resulting in suboptimal therapeutic outcomes due to factors such as poor ocular bioavailability, frequent dosing requirements, systemic side effects, and limited penetration through ocular barriers. This review elucidates the eye’s intricate anatomy and physiology, prevalent ocular diseases, traditional therapeutic modalities, and the inherent pharmacokinetic and pharmacodynamic limitations associated with these modalities. Subsequently, it delves into nanotechnology-based solutions, presenting breakthroughs in nanoformulations such as nanocrystals, liposomes, dendrimers, and nanoemulsions that have demonstrated enhanced drug stability, controlled release, and deeper ocular penetration. Additionally, it explores a range of nanosized carriers, including nano-structured lipid carriers, hydrogels, nanogels, nanoenzymes, microparticles, conjugates, exosomes, nanosuspensions, viral vectors, and polymeric nanoparticles, and their applications. Unique insights include emerging innovations such as nanowafers and transcorneal iontophoresis, which indicate paradigm shifts in non-invasive ocular drug delivery. Furthermore, it sheds light on the advantages and limitations of these nanotechnology-based platforms in addressing the challenges of ocular drug delivery. Though nano-based drug delivery systems are drawing increasing attention due to their potential to enhance bioavailability and therapeutic efficacy, the review ends up emphasizing the imperative need for further research to drive innovation and improve patient outcomes in ophthalmology. © The Author(s) 2025.